Solow and Heterogeneous Labor: A Neoclassical Explanation of Wage Inequality - Jürgen Meckl; Stefan Zink (Institute for the Study of Labor (IZA), 2003)
The paper analyzes the effect of human-capital investments of heterogeneous individuals on the dynamics of the wage structure within a neoclassical growth model. The accumulation of physical capital changes relative factor prices and thus incentives to acquire skills, thereby altering the composition of the labor force. Without relying on exogenous shocks, our framework generates dynamics that resembles several important observations on wage inequality (e.g., the non-monotone evolution of the skill premium). Additional incorporation of wage rigidities emphasizes the trade off between residual wage inequality and employment opportunities for unskilled labor that is consistent with country-specific evidence.
Keywords: I21; J31; O15; 330; wage inequality; human capital investment; transitional adjustment dynamics; skill-specific unemployment; Lohnstruktur; Qualifikation; Bildungsinvestition; Wachstumstheorie; Investition; Steady-State-Wachstum; Theorie